The effectiveness of model of teaching the integration of Indonesia-Thailand cultures in female basic dance movements through android-based media - Srinin, Wathanan; Lamnaokrut, Teerathorn; Riadil, Ikrar Genidal (Imaji: Jurnal Seni dan Pendidikan Seni, 2023)
The data analysis outcomes for establishing a teaching strategy for fundamental Thai Classical Dance based on Bloom's three-sided learning theory for the concept of teaching, which comprises cognitive, affective, and psychomotor learning, are revealed in this article. The study also incorporates Skinner's type R idea to provide a framework for study objectives and exercises in Fundamental Thai Classical Dance for students at Yogyakarta State University's Department of Dance Education in Indonesia. The strategy to teach Basic Thai Classical Dance via process based on the Teaching Model. The Integration of Indonesia-Thailand Cultures in Female Basic Dance Movement through Android-Based Media on four steps: 1) Background knowledge on the Basic Dance for Women and Thai Culture, 2) Training of the Basic Dance for Women in Thailand, 3) Connecting the cognitive, affective, and psychomotor aspects and 4) Dancing with songs. Implementing the Indonesian-Thai cultural integration learning model in the Thai Princess Basic Dance Movement through android-based media with applications. Students can gain cultural background knowledge and dance to songs in pairs with the basic elements of Wiraga, Wirasa, and Wirana dances and the context of Basic Thai Classical Dance for Women with effectiveness.Keywords: Model of Teaching Integration of Indonesia-Thailand Cultures, Process Implementations Basic Dance for Woman, Effectiveness of Model, Media Android Efektivitas model pengajaran integrasi budaya Indonesia-Thailand dalam gerakan tari dasar perempuan melalui media berbasis androidHasil analisis data untuk menetapkan strategi pengajaran Tari Klasik Thailand dasar berdasarkan teori pembelajaran tiga sisi Bloom untuk konsep pengajaran, yang terdiri dari pembelajaran kognitif, afektif, dan psikomotor, diungkapkan dalam artikel ini. Penelitian ini juga menggabungkan ide tipe R Skinner untuk menyediakan kerangka kerja untuk tujuan studi dan latihan Tari Klasik Thailand Dasar bagi mahasiswa di Jurusan Pendidikan Tari Universitas Negeri Yogyakarta di Indonesia. Strategi mengajar Tari Klasik Thailand Dasar melalui proses berdasarkan Model Pengajaran. Integrasi Budaya Indonesia-Thailand dalam Gerakan Tari Dasar Wanita Melalui Media Berbasis Android pada empat langkah: 1) Latar belakang pengetahuan Tari Dasar Wanita dan Budaya Thailand, 2) Pelatihan Tari Dasar Wanita di Thailand, 3) Menghubungkan aspek kognitif, afektif, dan psikomotorik dan 4) Menari dengan lagu. Menerapkan model pembelajaran integrasi budaya Indonesia-Thailand dalam Gerakan Tari Dasar Putri Thailand melalui media berbasis android dengan aplikasi. Siswa dapat memperoleh pengetahuan latar belakang budaya dan menari lagu berpasangan dengan elemen dasar tarian Wiraga, Wirasa, dan Wirana dan konteks Tari Klasik Thailand Dasar untuk Wanita dengan efektif.Kata Kunci: Keefektifan Model, Media Android, Model Pengajaran Integrasi Budaya Indonesia-Thailand, Proses Implementasi Tari Dasar Wanita